On the Optimal Pin Set Generation - Karol Grondzak; Juraj Branicky (Communications - Scientific letters of the University of Zilina, 2015)
Security of the information is one of the recent topics, attracting attention of security professionals as well as common people. With deep penetration of electronic devices into our everyday life the challenge to protect our privacy is increasing. Simple mechanism for authentication is shared secret in the form of password. In this paper we describe a method for generating a set of passwords in the form of Personal Identification Number (PIN), which can be used to provide an authentication mechanism for simple electronic devices with limited input possibilities.